2004
DOI: 10.1002/anie.200352125
|View full text |Cite
|
Sign up to set email alerts
|

Two Helical Conformations from a Single Foldamer Backbone: “Split Personality” in Short α/β‐Peptides

Abstract: Oligomers that adopt predictable conformations ("foldamers") are subjects of increasing interest from the perspectives of both fundamental research and applications.[1] The study of unnatural oligomers that display secondary structures analogous to those of proteins or nucleic acids provides new insight on the parameters that influence the "foldability" of a backbone, e.g., the relationships between conformational stability and number of residues or residue flexibility. As the rules that govern shape are eluci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
127
0
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(139 citation statements)
references
References 34 publications
9
127
0
3
Order By: Relevance
“…2,3 In particular, Fleet et al 4,5 have reported a number of peptidomimetics and unnatural biopolymers adopting interesting secondary structures because of the carbohydrate-derived tetrahydrofuran systems they contain. On their hand, the SeebachÕs 6,7 and GellmanÕs [8][9][10][11] groups have found that b-peptides are able to adopt defined three-dimensional structures similar to those of natural peptides. The unnatural b-peptide backbone is resistant to proteolysis, 2 in contrast to a-amino acid backbone.…”
Section: Introductionmentioning
confidence: 96%
“…2,3 In particular, Fleet et al 4,5 have reported a number of peptidomimetics and unnatural biopolymers adopting interesting secondary structures because of the carbohydrate-derived tetrahydrofuran systems they contain. On their hand, the SeebachÕs 6,7 and GellmanÕs [8][9][10][11] groups have found that b-peptides are able to adopt defined three-dimensional structures similar to those of natural peptides. The unnatural b-peptide backbone is resistant to proteolysis, 2 in contrast to a-amino acid backbone.…”
Section: Introductionmentioning
confidence: 96%
“…1 Em algumas áreas, os compostos heterocí-clicos são indispensáveis tanto para o funcionamento como para a eficiência de vários processos como, por exemplo, a obtenção de novas moléculas com atividade farmacológica, 2 desenvolvimento de polímeros, 3 além da produção de matérias primas industriais, como as ligas metálicas amorfas. 4 Com relação aos compostos formados por anéis de três membros, 5,6 em particular a aziridina (C 2 H 5 N), a elevada capacidade deste heterocíclico em reagir com nucleófilos é bem conhecida pelos químicos orgânicos, [7][8][9][10] podendo ser citado a esse respeito o mecanismo de síntese de Wenker.…”
Section: Introductionunclassified
“…The only crystallographically characterized examples are the structures of 8-and 11-aa peptides, in which a ␤␥ segment has been inserted into a peptide helix, with concomitant expansion of the hydrogen bonded rings at the site of insertion (6). Regular helical structures with mixed hydrogen bonds have been proposed from the NMR studies of alternating ␣͞␤ sequences, containing the stereochemically restricted ␤ residue trans-2-aminocyclopentanecarboxylic acid (ACPC) (7). As part of a program to insert segments containing multiple ␤ residues into ␣-peptide helices, we obtained the 11-aa peptide t-butoxycarbonyl (Boc)-Val-Ala-Phe-aminoisobutyric acid (Aib)-(R)-␤ 3 -homovaline (␤Val)-␤Phe-Aib-Val-Ala-Phe-Aib-OMe 1.…”
mentioning
confidence: 99%